Patterns of hypothalamic regionalization in amphibians and reptiles: common traits revealed by a genoarchitectonic approach - Domínguez, Laura; González, Agustín; Moreno, Nerea (Frontiers in Neuroanatomy, 2015)
Most studies in mammals and birds have demonstrated common patterns of hypothalamic development highlighted by the combination of developmental regulatory genes (genoarchitecture), supporting the notion of the hypothalamus as a component of the secondary prosencephalon, topologically rostral to the diencephalon. In our comparative analysis we have summarized the data on the expression patterns of different transcription factors and neuroactive substances, used as anatomical markers, in the developing hypothalamus of the amphibian Xenopus laevis and the juvenile turtle Pseudemys scripta. This analysis served to highlight the organization of the hypothalamus in the anamniote/amniotic transition. We have identified supraoptoparaventricular and the suprachiasmatic regions in the alar part of the hypothalamus, and tuberal and mammillary regions in the basal hypothalamus. Shared features in the two species are: 1) The supraoptoparaventricular region is defined by the expression of Otp and the lack of Nkx2.1/Isl1. It is subdivided into rostral, rich in Otp and Nkx2.2, and caudal, only Otp-positive, portions. 2) The suprachiasmatic area contains catecholaminergic cell groups and lacks Otp, and can be further divided into rostral (rich in Nkx2.1 and Nkx2.2) and a caudal (rich in Isl1 and devoid of Nkx2.1) portions. 3) Expression of Nkx2.1 and Isl1 define the tuberal hypothalamus and only the rostral portion expresses Otp. 4) Its caudal boundary is evident by the lack of Isl1 in the adjacent mammillary region, which expresses Nkx2.1 and Otp. Differences in the anamnio-amniote transition were noted since in the turtle, like in other amniotes, the boundary between the alar hypothalamus and the telencephalic preoptic area shows distinct Nkx2.2 and Otp expressions but not in the amphibian (anamniote), and the alar supraoptoparaventricular region is defined by the expression of Otp/Pax6, whereas in Xenopus only Otp is expressed.